2018
DOI: 10.1002/jum.14709
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐Care Ultrasound: Does it Affect Scores on Standardized Assessment Tests Used Within the Preclinical Curriculum?

Abstract: Point-of-care US program implementation may improve students' overall physical examination understanding and performance, even when US performance itself is not being tested. Introducing a POCUS curriculum may work best when designed in conjunction with the physical examination thread of a medical school curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
(68 reference statements)
2
18
1
1
Order By: Relevance
“…The likelihood that HHU devices will become ubiquitous outside the ED relatively soon has led some to suggest that US should become a routine part of the physical examination [ 3 ••, 40 , 62 ]. As US education is increasingly incorporated into medical school curricula, it is likely to make specialty-specific training and implementation at the graduate level easier and more widespread [ 5 , 63 65 ].…”
Section: Future Of Handhelds In the Edmentioning
confidence: 99%
“…The likelihood that HHU devices will become ubiquitous outside the ED relatively soon has led some to suggest that US should become a routine part of the physical examination [ 3 ••, 40 , 62 ]. As US education is increasingly incorporated into medical school curricula, it is likely to make specialty-specific training and implementation at the graduate level easier and more widespread [ 5 , 63 65 ].…”
Section: Future Of Handhelds In the Edmentioning
confidence: 99%
“…Indeed, the implementation of an ultrasound programme has been shown to improve overall understanding and performance of physical examination by medical students in an ultrasound education programme. 19 20…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the potential for long term clinical skills. [1,2] As the utility and scope of POCUS expands, it is important to ensure that physicians are competent with this technology and have a good understanding of the abilities and limitations of this imaging modality.…”
Section: Introductionmentioning
confidence: 99%